2012
DOI: 10.3844/ajessp.2012.510.522
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption From Aqueous Solution Onto Natural and Acid Activated Bentonite

Abstract: Dyes have long been used in dyeing, paper and pulp, textiles, plastics, leather, paint, cosmetics and food industries. Nowadays, more than 100,000 commercial dyes are available with a total production of 700,000 tones manufactured all over the world annually. About 10-15% of dyes are being disposed off as a waste into the environment after dyeing process. This poses certain hazards and environmental problems. The objective of this study is to investigate the adsorption behavior of Methylene Blue (MB) from aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 34 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The type of clay is indicated by the ratio of SiO 2 / Al 2 O 3 . For our sample, SiO 2 / Al 2 O 3 ratio is 3.14 which indicate the montmorillonite nature of clay 12,13 . This is also confirmed by XRD patterns of this sample.…”
Section: Resultsmentioning
confidence: 60%
“…The type of clay is indicated by the ratio of SiO 2 / Al 2 O 3 . For our sample, SiO 2 / Al 2 O 3 ratio is 3.14 which indicate the montmorillonite nature of clay 12,13 . This is also confirmed by XRD patterns of this sample.…”
Section: Resultsmentioning
confidence: 60%
“…Palanisamy et al (2012) reported the wavelength of maximum absorption (k max ) for Reactive Red 195 at 543 nm by UV-Vis spectrophotometer in their study ''Polymer Composite-A Potential Biomaterial for the Removal of Reactive Dye.'' Khatib et al (2012) determined characteristic absorbance of methylene blue using a single-beam UV-Vis spectrophotometer (Model SPUV-19) at a wavelength of maximum absorbance at 660 nm in their study ''Adsorption from aqueous solution onto natural and acid activated bentonite.'' Effect of pH on the sorption of RO 122 by T. bispinosa's peel and fruit…”
Section: Resultsmentioning
confidence: 99%
“…The physicochemical properties of the clay minerals can be modified by several methods such as the insertion of polyoxocations and pillars [13,14] or by means of acid treatment [15][16][17][18][19], increasing the specific surface area and the pore volume of the clays minerals. Franco et al have shown that, except for Hg(II), the Fe(III)-homoionic smectites display higher metal adsorption properties than that of activated carbon used previously [20].…”
Section: Introductionmentioning
confidence: 99%